"You are what you are in this world": visual framing and exemplification in media coverage of the Guttenfelder Instagram photographs from North Korea. (May 2019) - Holiday, Steven; Anderson, Harper D; Lewis, Matthew J; Nielsen, Rachel C
In 2013, photojournalist David Guttenfelder became one of the first people granted access to post images of life within North Korea to Instagram in real-time. This quantitative content analysis examines themes portrayed in Guttenfelder's Instagram photos and whether news sources that featured Guttenfelder's work proportionately represented the captured themes or perpetuated stereotypical views of North Korean totalitarianism. Results indicate significant differences in some sources' depictions of totalitarianism. The study discussed potential media and societal implications.